2007
DOI: 10.1038/sj.ki.5002376
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of hemodialysis vascular access flow using extracorporeal temperature gradients

Abstract: A reduction in vascular access flow poses a risk for thrombosis. We present a new technique to measure vascular access flow during dialysis based on extracorporeal temperature gradients, and their changes, on reversing the extracorporeal bloodlines without having to inject an indicator. Fistula temperatures were measured by the blood temperature monitor with normal line position and after manual switching of the bloodlines using the same extracorporeal blood flow. The access flow by our temperature gradient me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…Our results differ from those of Dias et al In our study, fistulae were cannulated with a distance of 2.5 cm between the two needles, whereas no mention of the exact distance between the needles was reported by Dias et al We used the thermodilution technique whereas Dias et al used the three blood‐urea sample method to calculate access recirculation. Urea‐based methods necessitate a lower blood flow than using the dialysis circuit: it is known to be inaccurate and can give false‐positive results . Non–urea‐based methods show more promise, but have still not been proven to impact on access longevity .…”
Section: Discussionmentioning
confidence: 99%
“…Our results differ from those of Dias et al In our study, fistulae were cannulated with a distance of 2.5 cm between the two needles, whereas no mention of the exact distance between the needles was reported by Dias et al We used the thermodilution technique whereas Dias et al used the three blood‐urea sample method to calculate access recirculation. Urea‐based methods necessitate a lower blood flow than using the dialysis circuit: it is known to be inaccurate and can give false‐positive results . Non–urea‐based methods show more promise, but have still not been proven to impact on access longevity .…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons with the saline dilution and ionic dialysance techniques have proven its validity for calculation of Qa. 13,26,27 A recent comparison of thermodilution (BTM), saline dilution (Transonic) and ionic dialysance (OCM) methods has demonstrated that the reproducibility of Qa measurements with the BTM does not significantly differ from that with Transonic: the Qa concordance (expressed as ICC, Intraclass Correlation Coefficients), the Qa correlation (r 2 ) and bias were 0.99 (P < 0.001), 0.98 (95% CI: 0.983, 0.995) and −19 ± 108 mL/min, respectively. 28 The BTM also has added advantages, such as lower work load, ease-of-performance, and its noninvasive character (i.e., no need for injection of indicators).…”
Section: Discussionmentioning
confidence: 99%
“…The continuous removal of these entities during extracorporeal treatments leads to distinctive arteriovenous gradients. If in presence of such gradients recirculation is induced by reversing blood lines, the concentrations and temperatures in arterial line blood are expected to change depending on the degree of recirculation (Schneditz et al 2007a, b;Wijnen et al 2007). As recirculation depends on access flow the change in temperatures and/or concentrations measured in the extracorporeal circulation can be used to calculate access flow without indicator injection, just from a simple line switch.…”
Section: Arterio-venous Gradientsmentioning
confidence: 99%